Technological approach in the organization of youth leisure activities (Journal of Educational Sciences, 2021)
he article discusses some issues related to implementing of the technological approach in the organization of the youth leisure. The relevance of the topic of the article is justified by the social order for the search for new approaches and technologies to the organization of youth leisure, the insufficient development of this problem in the scientific literature, the need to systematize the existing theoretical knowledge on this issue. The aim of the article is to give a theoretical justification of the technological approach in the organization of youth leisure. The theoretical analysis of the development of research studies considering this problem is presented. Some aspects of studying of the technologies practiced in the field of the youth leisure are highlighted. The author draws a parallel between pedagogical, sociocultural, and leisure technologies. The integrity of the technological process in cultural and leisure activities is considered in the interaction of such factors as the social order, goals, tasks, content, forms, methods of work, interaction of the subject and object, resource allocation, and commitment to final results. Special consideration is given to organizational aspects of the technological process in the cultural and leisure sphere. The definition of the technology of the youth leisure organizing is given. The component composition of the technology of the youth leisure organizing is determined; the systems that constitute its external environment are identified – this is the state educational, state youth and state cultural policy. The classification of technologies used in the organization of the youth leisure is presented.Key words: technological approach, technology of cultural and leisure activities, youth leisure activities, technology for organizing youth leisure activities.